Prevalence and correlates of firesetting behaviours among offending and non-offending youth - Watt, Bruce D. (Legal and criminological psychology, 2015)
Purpose Adolescents represent a disproportionate number of firesetters relative to their adult counterparts. There is limited understanding, however, in the differing rates of firelighting behaviours between subgroups of youth. Method Utilizing the recently developed Youth Fire Behaviours and Interests Scale, the differences in firesetting behaviours between adolescents adjudicated as offenders and non-offenders were evaluated. The associations for firesetting behaviours with antisocial behaviours and callous-unemotional traits (CUT) were examined utilizing items from the Antisocial Process Screening Device and the Strengths and Difficulties Questionnaire. Participants were recruited across south-east Queensland; young offenders on community orders or in a youth detention centre (n = 138), and adolescents from two private schools (n = 136). Results The young offender sample reported significantly higher prevalence of having lit a fire (67.4%) compared to non-offending youth (37.5%). Of concern, approximately one in five participants from both samples reported having lit 10 or more previous fires. Repeat firelighting behaviour in both samples was significantly predicted by history of antisocial behaviours, positive affect regarding fire, fire-related interests, and preoccupation with fire. CUT had a complex association with firesetting that was only statistically significant after accounting for fire-specific predictors. Findings from the current study are limited by the reliance on self-report measures without verification from carers or other collateral sources. Conclusion Interventions for preventing adolescent firesetting should include appraisal of general antisocial actions and more specific fire-interest characteristics. Further investigation of the association between CUT and firesetting is required before recommendations are proffered.